2018
DOI: 10.1039/c7py01069a
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of polymer topology and chain length on the antimicrobial activity and hemocompatibility of amphiphilic ternary copolymers

Abstract: Hyperbranched random copolymers that consist of ethylhexyl hydrophobic groups have the best selectivity compared to linear random and block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 56 publications
3
88
0
Order By: Relevance
“…Very recently, the same groups utilized ternary copolymer formulations (cationic, hydrophobic, and neutral/hydrophilic) to directly compare linear random versus block copolymers as well as hyper-branched analogues. 92 It was found that the hyper-branched polymers outperformed the linear copolymers in terms of cell-type selectivity.…”
Section: Emerging Sar Trendsmentioning
confidence: 99%
“…Very recently, the same groups utilized ternary copolymer formulations (cationic, hydrophobic, and neutral/hydrophilic) to directly compare linear random versus block copolymers as well as hyper-branched analogues. 92 It was found that the hyper-branched polymers outperformed the linear copolymers in terms of cell-type selectivity.…”
Section: Emerging Sar Trendsmentioning
confidence: 99%
“…However, the average molecular weight ( M n ) were not in agreement with M n values determined by GPC. Most of the cases M n determined by GPC was underestimated compared to values derived by NMR end group analysis . Suer et al also observed same phenomenon for polar phosponiumbased ROMP polymer .…”
Section: Resultsmentioning
confidence: 73%
“…It contains 30 repeat units of biocompatible oligoethylene glycol to impart low-fouling properties, 20 repeat units of hydrophobic ethylhexyl groups to induce membrane disruption, and 50 repeat units of primary amino groups to establish electrostatic interactions with bacterial membrane. 35,36 Scheme 1. Synthesis of antimicrobial polymer, P, which is an amphiphilic random ternary copolymer, via reversible addition−fragmentation chain transfer (RAFT) polymerization.…”
Section: Resultsmentioning
confidence: 99%